SOFTWARE DEFINED NETWORKING ARCHITECTURE FOR ENTERPRISE COMPUTER NETWORKS PERFORMANCE OPTIMIZATION - Fujita, Miku; Nishida, Daiki; Setiawan, Setiawan (Yayasan Adra Karima Hubbi, 2026)
The increasing complexity and demands of modern enterprise networks have highlighted the limitations of traditional network management systems. Network performance issues such as latency, congestion, and inefficient resource allocation have become significant challenges for businesses that rely on high-speed, reliable communication. Software Defined Networking (SDN) architecture has emerged as a promising solution to these challenges, offering centralized control, flexibility, and real-time optimization. This study investigates the impact of SDN architecture on the performance optimization of enterprise computer networks. The research aims to assess how SDN can improve network throughput, reduce latency, and enhance overall network efficiency in large-scale enterprise environments. A mixed-methods approach was employed, using both quantitative performance metrics and qualitative feedback from network administrators and IT managers. The results show a significant improvement in key network performance indicators, with throughput increasing by 30%, latency decreasing by 25%, and packet loss reducing by 18% after the implementation of SDN. The study concludes that SDN is a highly effective approach for optimizing network performance, offering greater scalability, security, and efficiency in enterprise settings. SDN enables real-time, dynamic network management, making it a crucial technology for modernizing enterprise network infrastructure.